FENOMENA LIVE STREAMING SEBAGAI TANTANGAN BARU DALAM ETIKA PENYIARAN MODERN - Puspa Ningrum, Dwi Handayany Puspa; Junaidi, Fazzar; Dwi Julyanti, Athika; Amalia Tsalitsa, Firly; Monica Renasva, Sherra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2024)
The development of live streaming on social media changes the broadcasting paradigm by offering freedom and interactivity, but raises new challenges regarding ethics and content control. This research aims to analyze the differences between conventional broadcasting which is strictly regulated by regulations and live streaming which is free and its impact on social norms and young audiences. Literature reviews are the main method for exploring these differences, including the influence of social media algorithms in driving sensational content. The results show that conventional broadcasting is more structured and able to maintain content quality, while live streaming often prioritizes engagement without strict controls, increasing the risk of spreading misinformation, inappropriate content, and the normalization of incompatible values. Young audiences are the most vulnerable group, affected by exposure to content that negatively impacts their self-image and behavior. The research conclusions highlight the importance of adaptive regulation, responsible algorithm development, and the role of parental and community education in mitigating negative impacts. This combination of approaches is necessary to maintain a balance between freedom of expression and social responsibility in modern broadcasting. Keywords: Live streaming, young audience, conventional, technology, social media.